Особливості оптимізації бізнес-процесів CALL CENTER - Радченко, Р. В. (ХНУРЕ, 2023)
Features of CALL CENTER business process optimization are presented on the basis of the proposed model, which includes directions for ensuring the parameters of efficiency and quality of user service. Achieving high KPI performance has allowed companies to maximize the productivity of their agents, expand their reach and, most importantly, deliver higher quality of customer service on an unprecedented scale. Taking into account all the methods implemented on the basis of theoretical research, it is possible to separate the main strategic directions that will help to improve the qualitative and qualitative parameters of the effectiveness of their activities.